PENGARUH MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN DIVISI FARMASI RUMAH SAKIT XYZ - Pamungkas, Yohanes Farrel; Ong Kim Kui , Daniel; Pramono, Rudy (Media Bina Ilmiah, 2024)
This research aims to identify the influence of intrinsic motivation and extrinsic motivation on employee performance with job satisfaction as an intervening variable. This research uses a quantitative method, where the data collection method is through a questionnaire process that is given online. The data collection technique used a purposive sampling technique where the respondents were employees of the Pharmacy Division of XYZ Hospital, Jakarta. The total sample for this research was 69 respondents. The statistical analysis method used in this research uses Smart PLS 4.0 software. Through the results of data processing, results are obtained 1) Intrinsic Motivation has a positive influence on Job Satisfaction, 2) Extrinsic Motivation has a positive influence on Job Satisfaction, 3) Intrinsic Motivation has a positive influence on Employee Performance, 4) Extrinsic Motivation has a positive influence on Employee Performance, 5) Job satisfaction does not have a positive influence on Employee Performance. 6) Intrinsic motivation does not have an indirect positive influence on employee performance through job satisfaction. 7) Extrinsic motivation does not have an indirect positive influence on employee performance through job satisfaction.